Case Report: Post-transplant lymphoproliferative disorder as a serious complication of vascularized composite allotransplantation - Zaccardelli, Alessandra; Lucas, Fabienne M.; LaCasce, Ann S.; Chandraker, Anil K.; Azzi, Jamil R.; Talbot, Simon G. (Frontiers in Transplantation, 2024)
We attach our manuscript entitled, "Post-transplant lymphoproliferative disorder as a serious complication of vascularized composite allotransplantation" for consideration for publication in Frontiers in Transplantation.While this aspect of VCA remains fairly uncommon, this appears to be the fourth known case. We believe that vigilance and a thorough understanding is important to all in our field. We have included a broad review of the literature including the most up-to-date treatment algorithm which will apply to all types of transplantation.